A thermal-hydraulic-mechanical coupling model for freezing process simulation of cementitious materials with entrained air voids. (20th May 2020) - Dong, Yijia; Su, Chao; Qiao, Pizhong; Sun, Lizhi
Highlights: A thermal-hydraulic-mechanical model is proposed to study the freezing process. Volume of capillary water expelled into each entrained air void is determined. Distributions of temperature, pore pressure and strain are simulated upon freezing. Abstract: Frost resistance of cementitious materials is enhanced with introduction of a series of randomly-dispersed air-entrained voids. While it is understood that the improvement of frost resistance is due to the functions of cryo-suction and water reservoir of the voids, their heterogeneous, random distribution has not been considered in the modeling framework to investigate the material responses during freezing process. In this paper, a thermal-hydraulic-mechanical coupling model is proposed to study the responses of temperature, pore pressure and deformation of cementitious materials with randomly-distributed air voids. The entire freezing process is simulated with consideration of thermal, mechanical, and seepage boundary conditions of cementitious materials. The predictions achieve satisfactory consistency with previous experimental results from the overall freezing deformation of mortar. The filling effect of entrained air voids by expelled water is also assessed. Finally, the proposed model is used to analyze the influence of cooling rate on the freezing of mortar.